2018
DOI: 10.2306/scienceasia1513-1874.2018.44.388
|View full text |Cite
|
Sign up to set email alerts
|

Production potential of tidal flats for blood clam (Anadara granosa) culture in Bang-tabun bay, Phetchaburi province

Abstract: Production potential of blood clam (Anadara granosa) in Bang-tabun Bay was examined by integrating data for size distribution, growth rate, and aquatic environmental factors. Collection of data was conducted from December 2011 to May 2012. Blood clam culture areas from three muddy tidal flats; Don Bon flat, Don Klang flat, and Don Tuen flat located from the north to the south of the bay, respectively, were studied. Length and weight of clams at each station varied each month depending on the growth potential o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…The result of this study showed that when the salinity of seawater was higher than 19 psu, the production potential of cockles was quite high and the growth rate of cockle was 0.86-4.68 g/month ( Table 4) . Our results are in agreement with the research on the production potential of tidal flats for blood clam (Anadara granosa) culture in Bang Taboon Bay, Petchaburi province by Srisomwong et al [10]. They reported that the optimum salinity level for cockle growth was approximately 20 psu.…”
Section: Salinity Of Seawatersupporting
confidence: 93%
See 2 more Smart Citations
“…The result of this study showed that when the salinity of seawater was higher than 19 psu, the production potential of cockles was quite high and the growth rate of cockle was 0.86-4.68 g/month ( Table 4) . Our results are in agreement with the research on the production potential of tidal flats for blood clam (Anadara granosa) culture in Bang Taboon Bay, Petchaburi province by Srisomwong et al [10]. They reported that the optimum salinity level for cockle growth was approximately 20 psu.…”
Section: Salinity Of Seawatersupporting
confidence: 93%
“…In this study, blood cockle growth rate (g/month) was evaluated for the production potential of cockles [10]. Blood cockle size was determined by measuring three shell axes as length, height and width (Figure 2) as described by Şahı̇n et al [11].…”
Section: Blood Cockle Analysismentioning
confidence: 99%
See 1 more Smart Citation